ANALISIS PENGARUH FINANCIAL LEVERAGE, UKURAN, JENIS AUDITOR, PROFITABILITAS, UMUR, DAN RISIKO TERHADAP PENGUNGKAPAN LAPORAN PERUSAHAAN MANUFAKTUR PERIODE 2011 – 2014 - Marini Marini; Synthia Madya Kusumawati (Universitas Bunda Mulia, 2017)
This study aims to empirically eximine the factors that affect the level of financial statements discosure, using financial leverage, size, auditor type, profitability, age, and risk as independent variable.This study was conducted using multiple regression analysis and data processing with the E - views 6.0 program. The data in this research is secondary data obtained from the audited financial statements for 2010-2014 and the annual report for 2011-2013. The population in this study amounted to 141 companies, which obtained a sample of 69 companies and 207 units of observation (69 companies multiplied by 3 years).The results from this study indicate that there are two independent variables to be significant with level of disclosure of firm report , financial leverage to be negative significant for determining the level disclosure and firm size has a positive significant with the level disclosure. While 4 other variables, auditor type, the profitability, firm age and firm risk insignificant with the level of disclosure.Key words : financial statement disclosure, leverage, size, auditor type, profitability, age, risk